Luster - Leilani, Raven (Farrar, Straus and Giroux, 2020)
Edie is stumbling her way through her twenties- sharing a subpar apartment in Bushwick, clocking in and out of her admin job, making a series of inappropriate sexual choices. She is also haltingly, fitfully giving heat and air to the art that simmers inside her. And then she meets Eric, a digital archivist with a family in New Jersey, including an autopsist wife who has agreed to an open marriage- with rules. As if navigating the constantly shifting landscapes of contemporary sexual manners and racial politics weren't hard enough, Edie finds herself unemployed and invited into Eric's home- though not by Eric. She becomes a hesitant ally to his wife and a de facto role model to his adopted daughter. Edie may be the only Black woman young Akila knows. Luster is a portrait of a young woman trying to make sense of her life- her hunger, her anger- in a tumultuous era. It is also a description of how hard it is to believe in your own talent, and the unexpected influences that bring us into ourselves along the way.